Qur’anic Perspectives on Economic Ethics: A Thematic Study of Four Key Verses for Building a Prosperous Ummah - Ningsih, Fitiriah; Muntu, Andi Tenri Sri; Ilham, Muhammad; Ridwan; Masse, Rahman Ambo (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2025)
This study conducts a thematic exegesis (tafsir maudhū‘ī) of Qur’anic verses related to investment, focusing on four key verses. Surah Al‑Baqarah (2): 261, An‑Nisā’ (4): 9, Luqmān (31): 34, and Al‑Hashr (59): 18. A library-based methodology is employed, integrating thematic interpretation, linguistic analysis, the contexts of revelation (asbāb al‑nuzūl), and inter-verse correlations (munāsabah). Findings reveal that Islamic investment is not solely about wealth accumulation; it emphasises ethical commitment, justice, and social welfare. This Qur’anic framework offers a foundation for Islamic economic models that harmonise financial efficiency with public welfare and balance worldly gains with accountability before the Hereafter. The study’s insights contribute to the development of Sharia-compliant economic policies and investment practices that promote prosperity and social justice.